Why asylum seekers deserve better healthcare, and how we can give it to them. (6th January 2022) - Farrant, Olivia; Eisen, Sarah; van Tulleken, Chris; Ward, Allison; Longley, Nicky
Abstract : Many asylum seekers in the UK find themselves in a purgatory of paperwork that leaves a total absence of healthcare. Olivia Farrant and colleagues explain how, in the depths of the pandemic, a model response was born